2021
DOI: 10.1002/smll.202007389
|View full text |Cite
|
Sign up to set email alerts
|

Fabrications of High‐Performance Planar Zinc‐Ion Microbatteries by Engraved Soft Templates

Abstract: Miniaturized energy storage devices (MESDs) provide future solutions for powering dispersive electronics and small devices. Among them, aqueous zinc ion microbatteries (ZIMBs) are a type of promising MESDs because of their high‐capacity Zn anode, safe and green aqueous electrolytes, and good battery performances. Herein, for the first time, a simple and powerful strategy to fabricate flexible ZIMBs based on tailored soft templates is reported, which are patterned by engraving and enables to design the ZIMBs fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 45 publications
0
57
0
Order By: Relevance
“…Jiang et al reported flexible zinc ion microbatteries with the α-MnS cathode. 7 The as-prepared microbatteries delivered a high areal capacity of 178 μA h cm −2 and an energy density of up to 322 μW h cm −2 at the power density of 120 μW cm −2 . These pioneering research efforts show feasibility and suitability of MnS as zinc ion batteries' cathode material.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Jiang et al reported flexible zinc ion microbatteries with the α-MnS cathode. 7 The as-prepared microbatteries delivered a high areal capacity of 178 μA h cm −2 and an energy density of up to 322 μW h cm −2 at the power density of 120 μW cm −2 . These pioneering research efforts show feasibility and suitability of MnS as zinc ion batteries' cathode material.…”
Section: Introductionmentioning
confidence: 97%
“…3,4 The rechargeable aqueous metal ion batteries, which are assembled with aqueous solution electrolyte and earth abundant metal anode (e.g., Zn, Mg, and Al), are being revived due to their advantages of simple and convenient assembly, admirable security, and decent ionic conductivity. [5][6][7] Among them, the rechargeable zinc ion battery has aroused considerable attention due to its admirable safety, cost-effectiveness, moderate redox potential (−0.76 V vs. SHE), and decent theoretical capacity (∼820 mA h g −1 ) of the Zn anode. 6,8,9 However, the zinc ion battery is still in its infancy, and one of the core tasks aim to prompt the development of the zinc ion battery is to screen out competent cathode materials that can sustainably serve for repeated Zn 2+ intercalation/deintercalation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Besides, this microdevice also shows a small series resistance (Figure S14, Supporting Information). At the low current density of 2 mA cm −2 , a maximum areal specific capacity of 1932.3 μAh cm −2 is achieved (Figure 3f,g; Table S1, Supporting Information), far exceeding those of all reported aqueous MBs, [15][16][17][19][20][21][22][23][52][53][54][55][56][57] highperformance organic MBs (lithium-ion MBs, [12,24,58,59] sodiumion MBs, [60] and dual-ion MBs [61] ), state-of-the-art zinc-ion MSCs, [62,63] and lithium-ion MSCs [64] (Figure 3i). Even at higher current densities of 8 and 10 mA cm −2 , it still exhibits excellent areal specific capacity of 622.43 and 407 μAh cm −2 with high Coulombic efficiency of 97.4% and 98.1%, respectively (Figure 3f,g).…”
Section: mentioning
confidence: 88%
“…The other type of paper zinc‐ion batteries employs the paper only as the substrate, in which the batteries are in‐plane printed on one side and present interdigitated configuration. [ 28 , 29 ] Printing electrode inks on both sides is challenging because it may cause short of the battery due to the rough and permeable surface of paper. Accordingly, the printed micro‐batteries on paper deliver limited areal capacity and volumetric energy density (up to ≈10 mWh cm –3 ).…”
Section: Introductionmentioning
confidence: 99%